2016
DOI: 10.1371/journal.pone.0156085
|View full text |Cite
|
Sign up to set email alerts
|

Protein Carbonyl as a Biomarker of Oxidative Stress in Severe Leptospirosis, and Its Usefulness in Differentiating Leptospirosis from Dengue Infections

Abstract: Pathogenesis of disease severity in leptospirosis is not clearly understood whether it is due to direct damage by pathogen or by adverse immune responses. Knowledge on biomarkers of oxidative stress which could be used in identifying patients with severe illness has shown to be of great value in disease management. Thus, the main aim of this study was to assess the damage to serum proteins and lipids, and their significance as biomarkers of oxidative stress in severe leptospirosis. In regions endemic for both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
23
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 40 publications
3
23
0
1
Order By: Relevance
“…There are different biomarkers to assess the redox status of tissues including free radicals, lipid peroxidation products and alterations of antioxidant levels (as a surrogate marker). In this study serum nitrites, nitrates and TAOC were used as these assays have been used and validated for the local population previously for non-asthma related pathologies including leptospirosis [ 28 , 35 , 37 ], dengue haemorrhagic fever [ 34 ] and Parkinson disease [ 38 ]. Other studies which measured pro-oxidant levels in patients with asthma used exhaled nitric oxide (eNO) as this is a sensitive and specific marker of airway inflammation and a higher level of eNO was recorded in patients with asthma as compared to healthy controls [ 39 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are different biomarkers to assess the redox status of tissues including free radicals, lipid peroxidation products and alterations of antioxidant levels (as a surrogate marker). In this study serum nitrites, nitrates and TAOC were used as these assays have been used and validated for the local population previously for non-asthma related pathologies including leptospirosis [ 28 , 35 , 37 ], dengue haemorrhagic fever [ 34 ] and Parkinson disease [ 38 ]. Other studies which measured pro-oxidant levels in patients with asthma used exhaled nitric oxide (eNO) as this is a sensitive and specific marker of airway inflammation and a higher level of eNO was recorded in patients with asthma as compared to healthy controls [ 39 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…High levels of protein carbonyl (>C=O) groups have been observed in some diseases, including Alzheimer's disease (AD), rheumatoid arthritis, diabetes, sepsis, chronic renal failure, and respiratory distress syndrome (Pullaiah et al, 2018). In microbial infections (e.g., leptospirosis), induced oxidative stress like the protein carbonyls are of diagnostic value (Fernando et al, 2016). Also, it was reported that urinary 8-hydroxy-2-deoxyguanosine (8-OHdG), an oxidized nucleoside of DNA, is a DNA oxidative stress biomarker and a risk factor for cancer, atherosclerosis, and diabetes (Wu et al, 2004; Kawai et al, 2018).…”
Section: Types Of Biomarkersmentioning
confidence: 99%
“…We also included 30 patients with critical phase dengue, and 30 healthy controls (table 5). 36 Lipid peroxide levels were measured using the Ferrous Oxidation-Xylenol orange (FOX2) assay. Our findings showed that lipid peroxide levels were high in patients with leptospirosis, and were low in patients with dengue and healthy controls.…”
mentioning
confidence: 99%